Assessment of fire-damaged concrete structures using color image analysis a case study - Miranda, Nicole C.
A new method is developed using color image analysis with an ordinary digital camera, to assess the condition of fire-exposed concrete. When subjected to elevated temperatures, concrete experiences physical and chemical changes which may affect the serviceability of the structure. In this research, the point-by-point responses of small concrete samples are checked using the new method of analyzing color changes in the concrete. Color change provides an indicator of the maximum experienced temperature which in turn aids in estimating the mechanical and physical residual properties of the fire-exposed concrete. In particular, relative hue value (RHV) changes are investigated from photographs of the cross section of 3-inch diameter concrete cores that are obtained, for example, from the fire-damaged UPD Palma Hall Pavilion II (Chemistry). In this case, the concrete in the columns that are examined is found to be sound but with significantly reduced strength. Such assessment is primarily important because insurance companies want to know the value of repairs, while building owners value the speed of restoration of service. Without relying on visual assessment by special inspectors, the newly developed method is easy to implement; it is fast and economical.